(untitled) (Swiss Medical Weekly, 2023)
AIMS OF THE STUDY: Globally, since the introduction of conjugate-vaccines against encapsulated bacteria, respiratory viruses have caused most hospitalisations for community-acquired pneumonia. The aim of this study was to describe pathogens detected and their association with clinical findings in Switzerland. METHODS: Baseline data were analysed for all trial participants enrolled between September 2018 and September 2020 into the KIDS-STEP Trial, a randomised controlled superiority trial on the effect of betamethasone on clinical stabilisation of children admitted with community-acquired pneumonia. Data included clinical presentation, antibiotic use and results of pathogen detection. In addition to routine sampling, nasopharyngeal specimens were analysed for respiratory pathogens using a panel polymerase chain reaction test covering 18 viral and 4 bacterial pathogens. RESULTS: 138 children with a median age of 3 years were enrolled at the eight trial sites. Fever (obligatory for enrolment) had been present for median 5 days before admission. Most common symptoms were reduced activity (129, 93.5%) and reduced oral intake (108, 78.3%). Oxygen saturation <92% was found in 43 (31.2%). Forty-three participants (29.0%) were already on antibiotic treatment prior to admission and 104 participants (75.4%) received antibiotic treatment on admission. Pathogen testing results were available from 132 children: 31 (23.5%) had respiratory syncytial virus detected, 21 (15.9%) human metapneumovirus. The pathogens detected showed expected seasonal and age preponderance and were not associated with chest X-ray findings. CONCLUSIONS: In the context of the predominantly viral pathogens detected, the majority of antibiotic treatment is probably unnecessary. The ongoing trial, as well as other studies, will be able to provide comparative pathogen detection data to compare pre- and post-COVID-19-pandemic settings.